Forest biomes of Southern Africa. Issue 4 (2nd October 2022) - Mucina, Ladislav; Lötter, Mervyn C.; Rutherford, Michael C.; van Niekerk, Adriaan; Macintyre, Paul D.; Tsakalos, James L.; Timberlake, Jonathan; Adams, Janine B.; Riddin, Taryn; Mccarthy, Lauren K.
ABSTRACT: The forests of South Africa and the neighbouring countries, including Lesotho, eSwatini, Namibia, Botswana, Zimbabwe, and Mozambique (south of the Zambezi River), were mapped and classified according to the global system of biomes. The new four-tier hierarchical biome system suggested in this paper includes zonobiome, global biome, continental biome (all recognised earlier), and regional biome – a novel biome category. The existing spatial coverages of the forests were revised and considerably improved, both in terms of forest-patch coverage and mapping precision. Southern Africa is home to three zonal forest types, namely Subtropical Forests (Zonobiome I), Tropical Dry Forest (TDF; Zonobiome II) and Afrotemperate Forests (Zonobiome X). These three biomes are characterised by unique bioclimatic envelopes. Five, two, and eight regional biomes, respectively, have been recognised within these zonal biomes. Recognition of the Zonobiome I and the global biome Tropical Dry Forests in southern Africa is novel and expands our knowledge of the biome structure of African biotic communities. The system of the azonal regional biomes is also new and comprehensively covers the variability of the azonal helobiomes (riparian woodlands and swamp forests), mangroves, and azonal coastal forests. In total, 11 azonal regional biomes have been recognised in the study area. The forest biomes in southern Africa were captured in our electronic map in the form of more than 60 000 polygons, covering 42 416 km 2 (1.27% of the study area). No less than 83% of these forests occur in the territory of southern Mozambique. Abbreviations: for the abbreviation of the biome units, see Table 1 ; CE: centre of endemism; IOCB: Indian Ocean Coastal Belt; MBSA: the area of the Map of Biomes of Southern Africa; VegMap2006 and VegMap2018: Vegetation Map of South Africa, Lesotho and Swaziland (as released in respective years); for the meaning of the codes of the biome units see Table 1, and for the meaning of the abbreviations of climatic characteristics see Appendix S1